The lightweight design of steel pistons for diesel engines based on thermo-mechanical characteristics - Yang Liu; Jilin Lei; Jikun Chen; Weiwei Gao; Hu Peng; Jianrui Wang (Scientific Reports)
Abstract Traditional aluminum–silicon alloy pistons are gradually replaced by steel pistons, which has become the trend of future diesel engine development. However, the efficient design and broad application of steel pistons are limited by the higher density of steel. For this reason, a new lightweight design method for steel pistons in diesel engines was proposed in this paper. The progressive design of the cooling gallery cross-section and the topology optimization of the window region were carried out to meet the strength and deformation requirements. Ultimately, a lightweight steel piston (LSP) was obtained. The results of the study showed that the total mass of LSP could be reduced by 8.86% compared to the original steel piston (OSP). The thermal states of LSP are all superior to those of OSP. The highest temperature, maximum thermal stress, maximum longitudinal thermal deformation, and maximum transverse thermal deformation can be reduced by 0.96 °C, 3.03%, 11.65%, and 8.99%, respectively. LSP has a larger thermo-mechanical coupling stress manifestation compared to OSP. However, the maximum longitudinal and transverse thermo-mechanical coupling deformations can be obtained with a significant reduction of 8.33% and 42.19%, respectively.